Preparation method and application of composite thermal insulation material for inhibiting thermal runaway propagation of lithium ion battery
By introducing a composite thermal insulation material of nano-hydroxyapatite, boron carbide nanosheets and glass fiber into lithium-ion batteries, the problem of poor suppression of thermal runaway propagation in lithium-ion batteries in existing technologies is solved, achieving more efficient thermal management and safety protection.
Patent Information
- Application Number
- CN202510835548.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-20
- Publication Date
- 2025-09-16
- Estimated Expiration
- 2045-06-20
AI Technical Summary
Existing methods for suppressing the propagation of thermal runaway in lithium-ion batteries have problems such as high cost, increased weight, and poor mechanical properties. A single thermal insulation material cannot effectively suppress the propagation of thermal runaway between batteries.
Sodium alginate and polyvinyl alcohol are used as the matrix, and nano-hydroxyapatite, boron carbide nanosheets and glass fiber are added to form a composite thermal insulation material through electrostatic attraction and coordination bonds. The high thermal conductivity of boron carbide and the thermal insulation of glass fiber are combined to form a thermal conductivity-insulation synergistic mechanism.
It significantly improves the mechanical strength and thermal insulation effect of the composite thermal insulation material, effectively delays the triggering time of thermal runaway, reduces the peak temperature of the runaway battery, and controls the temperature rise rate of the non-runaway battery.
Smart Images

Figure CN120657324A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery safety protection, and in particular to a preparation method and application of a composite thermal insulation material for inhibiting the propagation of thermal runaway of lithium-ion batteries. Background Art
[0002] As a rechargeable battery, lithium-ion batteries (LIBs) demonstrate significant advantages in mobile electronic devices and new energy vehicles due to their high energy density, long cycle life, low self-discharge rate, and excellent cycle stability. With the rapid advancement of technology, these batteries are also facing new challenges in terms of safety performance, especially the increasingly prominent phenomenon of thermal runaway. When batteries are subjected to abnormal operating conditions such as external impact, overcharge, over-discharge, or high temperature environments, they can easily trigger a chain reaction of exothermic reactions and release huge amounts of heat energy. At the same time, internal short circuits caused by battery performance degradation or manufacturing defects can also expose battery management systems to the risk of unpredictable thermal runaway. Especially in multi-battery pack applications such as electric vehicles, thermal runaway of a single battery often triggers a chain reaction in densely packed battery modules, which may ultimately cause serious accidents in the entire power system.
[0003] How to delay and suppress the propagation of thermal runaway (TRP) between battery packs is one of the major unresolved safety-related issues in battery packs. Many scholars have proposed different methods to suppress TPP, mainly five of which are: (1) Active battery cooling using coolants (e.g., water, air), which are usually laid in hoses, pipes, or microchannels in the battery system. Due to its complexity, this method is costly and may occupy a large volume of battery modules and battery packs. In addition, it cannot provide sufficient cooling energy to prevent TPP. (2) Using the thermal capacity of the battery system to provide rapid heat dissipation by contacting the battery with a high thermal conductivity material. The main disadvantage of this method is the increase in battery pack weight, which reduces the energy density of the battery system and its limitation to low-capacity batteries. (3) Thermal insulation between batteries, which limits thermal runaway to a single battery. However, thermal insulation cannot completely suppress TPP between batteries because the energy density of LIBs continues to increase, so the cells in TR release higher energy, and the thermal shock generated when the battery undergoes TR will directly lead to the destruction of the thermal insulation material, thereby reducing its continuous thermal insulation effect. (4) Use of phase change materials (PCM). In this method, PCM partially absorbs the released TR energy through an endothermic phase change (solid to liquid) at 50-90°C. One of the main disadvantages of this method is the flash point of the commonly used paraffin wax, which significantly increases the fire load in the case of TR. (5) Hydrogel materials are used to suppress TRP between battery modules. Due to their good biocompatibility and extremely high water content, they have many advantages in suppressing TRP. However, hydrogels generally have poor mechanical properties and cannot effectively cope with the extrusion collision caused by battery TR.
[0004] In summary, a single thermal insulation material cannot effectively solve the safety issues caused by TRP between batteries. This shows that the existing technology needs further improvement. Summary of the Invention
[0005] One of the objectives of the present invention is to provide a method for preparing a composite thermal insulation material that inhibits the propagation of thermal runaway in lithium-ion batteries. By optimizing the method, the mechanical strength and thermal insulation effect of the composite thermal insulation material can be improved, and the risk of thermal runaway in lithium-ion battery modules can be more effectively suppressed.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a composite thermal insulation material for inhibiting the propagation of thermal runaway of a lithium-ion battery comprises the following steps:
[0008] a. mixing the sodium alginate solution and the polyvinyl alcohol solution to obtain a mixed solution 1;
[0009] b. Adding nano-hydroxyapatite to the mixed solution 1 and placing it in an ultrasonic device for ultrasonic treatment, then placing the ultrasonically treated mixed solution in a water bath at 50-60° C. to ensure that the nano-hydroxyapatite is evenly dispersed, to obtain a mixed solution 2;
[0010] c. adding acrylamide and 2-acrylamide-2-methylpropanesulfonic acid to the mixed solution II in sequence, and stirring uniformly to obtain a mixed solution III;
[0011] d. Adding boron carbide nanosheets to the mixed solution (3), adjusting the pH to 5-7, and fully stirring under certain temperature conditions to obtain a mixed solution (4). The phosphate in the nanohydroxyapatite and the cations on the surface of the boron carbide generate electrostatic attraction to form ionic bonds, and the boron atoms on the surface of the boron carbide form coordination bonds with the oxygen in the phosphate or hydroxide of the nanohydroxyapatite.
[0012] e. Adding glass fiber to the mixed solution (4) and placing the solution in an ultrasonic device for ultrasonic treatment. Then, placing the resulting mixed solution in a water bath at 50-60° C. to ensure uniform dispersion of the glass fiber, thereby obtaining a mixed solution (5);
[0013] f. Slowly add ammonium persulfate as an initiator to the mixed solution five, activate the active functional groups of sodium alginate, polyvinyl alcohol, acrylamide, and 2-acrylamide-2-methylpropanesulfonic acid through the ammonium persulfate, cause a chain reaction and form a long-chain structure, then add a cross-linking agent to the resulting hydrogel system to react, introduce glass fiber into the hydrogel system through cross-linking, and form a "thermal conduction-thermal insulation" mechanism due to the thermal conductivity of boron carbide and the thermal insulation of glass fiber to obtain a composite thermal insulation material.
[0014] The above-mentioned method for preparing a composite insulation material for inhibiting the propagation of thermal runaway of a lithium-ion battery, in step a, the mass fraction ratio of the sodium alginate solution to the polyvinyl alcohol solution is 0.8:1; the sodium alginate solution is prepared by adding sodium alginate to deionized water, the mass volume ratio of sodium alginate to deionized water is 1.6:300 g / L, and the dissolution temperature is 70-75°C; the polyvinyl alcohol solution is prepared by adding polyvinyl alcohol to deionized water, the mass volume ratio of polyvinyl alcohol to deionized water is 2:300 g / L.
[0015] In the above-mentioned method for preparing a composite thermal insulation material for inhibiting the propagation of thermal runaway of lithium-ion batteries, in step b, the mass ratio of nano-hydroxyapatite to sodium alginate is 1:1.
[0016] In the above-mentioned method for preparing a composite thermal insulation material for inhibiting the propagation of thermal runaway in lithium-ion batteries, in step c, the mass ratio of acrylamide to sodium alginate is 1:0.4, and the mass ratio of acrylic amine to 2-acrylamide-2-methylpropanesulfonic acid is 2:1; the temperature is maintained at 50-60°C during stirring.
[0017] In the above-mentioned method for preparing a composite thermal insulation material for inhibiting the propagation of thermal runaway of lithium-ion batteries, in step d, the mass ratio of the added amount of boron carbide nanosheets to 2-acrylamide-2-methylpropanesulfonic acid is 1:1, and the temperature is controlled at 50-60°C during stirring.
[0018] In the above-mentioned method for preparing a composite thermal insulation material for inhibiting the propagation of thermal runaway of a lithium-ion battery, in step e, the mass ratio of the glass fiber to the boron carbide is 5:2.
[0019] In the above-mentioned method for preparing a composite thermal insulation material for inhibiting the propagation of thermal runaway in lithium-ion batteries, in step f, the mixed solution five is placed in a constant temperature water bath at a temperature of 60-65°C, and the mass ratio of ammonium persulfate to glass fiber is 0.009:1.
[0020] In the above-mentioned method for preparing a composite thermal insulation material for inhibiting the propagation of thermal runaway in lithium-ion batteries, in step f, the cross-linking agent is N,N-methylenebisacrylamide, the mass ratio of the added amount of N,N-methylenebisacrylamide to ammonium persulfate is 0.38:0.045, the reaction temperature after adding the cross-linking agent is 60-65°C, and the reaction is carried out for 2-4 hours.
[0021] Another object of the present invention is to provide an application of a composite thermal insulation material prepared by the above-mentioned preparation method, characterized in that: when the composite thermal insulation material is in direct contact with a heat source, it can effectively delay the triggering time of thermal runaway, reduce the peak temperature of the runaway battery and effectively control the temperature rise rate of the non-runaway battery.
[0022] Compared with the prior art, the present invention brings the following beneficial technical effects:
[0023] The present invention proposes a method for preparing a composite thermal insulation material for inhibiting the propagation of thermal runaway of lithium-ion batteries, wherein sodium alginate and polyvinyl alcohol are used as a matrix, and acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, nano-hydroxyapatite and glass fiber are used as a matrix, wherein the nano-hydroxyapatite and glass fiber are synergistically composited to enhance the thermal insulation performance. Boron carbide nanosheets are introduced into the hydrogel system, and the high thermal conductivity of boron nitride is used to directionally guide local hot spots, and synergistically form a "thermal conduction-thermal insulation" synergistic mechanism with glass fiber. Specifically, the phosphate (PO43-) in the nano-hydroxyapatite and the cations (such as B 3+ ) generates electrostatic attraction, forming ionic bonds; the boron atoms (B) on the boron carbide's surface form coordination bonds with the oxygen atoms in the PO43- or OH- atoms of the nanohydroxyapatite. This, in turn, synergizes with the nanohydroxyapatite to enhance the hydrogel's thermal insulation. Boron carbide's high thermal conductivity can channel localized hotspots, creating a synergistic "thermal conductivity-insulation" mechanism with glass fiber.
[0024] The composite thermal insulation material prepared by the present invention has excellent mechanical strength and thermal insulation effect, and can effectively suppress the risk of thermal runaway of lithium-ion battery modules. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The present invention will be further described below with reference to the accompanying drawings:
[0026] Figure 1 This is a schematic structural diagram of the thermal runaway experimental device of the present invention;
[0027] Figure 2 (a) is a scanning electron microscope image of glass fiber, (b) is a scanning electron microscope image of hydroxyapatite; (c) is a scanning electron microscope image of the hydrogel obtained without adding glass fiber; (d) and (e) are scanning electron microscope images of the composite thermal insulation material prepared by the present invention; (f) is a transmission electron microscope image of the composite thermal insulation material prepared by the present invention.
[0028] Figure 3 (a) and (b) are the thermal stability test results of composite insulation materials obtained with different hydroxyapatite addition amounts.
[0029] Figure 4 (a) and (b) are the compressive properties of composite insulation materials obtained with different hydroxyapatite addition amounts.
[0030] Figure 5 This is a temperature response analysis diagram of the thermal runaway propagation experiment. Specifically, the heating rod is located in the center. Under the condition of no protection, the temperature change curve of each battery during the TR propagation experiment is as a function of time;
[0031] Figure 6 This is a temperature response analysis diagram of the thermal runaway propagation experiment, specifically, the temperature change curve of each battery during the TR propagation experiment is shown with the heating rod located in the center and protected by a 4mm thick composite thermal insulation material of the present invention;
[0032] Figure 7 The temperature variation curve of each cell during the TR propagation experiment without protection when the heating rod is located at the side;
[0033] Figure 8 The temperature variation curve of each cell during the TR propagation experiment is shown as a function of time when the heating rod is located at the side and protected by a 4 mm composite thermal insulation material of the present invention.
[0034] Figure 9 The temperature variation curve of each cell during the TR propagation experiment without protection when the heating rod is located at the corner;
[0035] Figure 10 The temperature variation curve of each battery during the TR propagation experiment is shown as a function of time when the heating rod is located at the corner and protected by the 4 mm thick composite thermal insulation material of the present invention. DETAILED DESCRIPTION
[0036] The present invention provides a preparation method and application of a composite thermal insulation material for inhibiting the propagation of thermal runaway in lithium-ion batteries. In order to make the advantages and technical solutions of the present invention clearer and more specific, the present invention is further described below with reference to specific embodiments.
[0037] The raw materials described in the present invention can all be purchased through commercial channels.
[0038] The main technical concept of the present invention is: in view of the limitations of single thermal insulation materials in practical applications, a new type of composite thermal insulation material has been developed in a targeted manner to optimize its performance. Hydrogels have shown significant advantages in the fields of thermal management and thermal runaway propagation suppression due to their unique three-dimensional network structure, excellent water absorption and retention capacity, and simple preparation process. The present invention significantly improves the mechanical properties and thermal stability of composite thermal insulation materials by optimizing the skeleton structure of hydrogels. On this basis, physical cross-linking technology is used to introduce glass fibers with low thermal conductivity into the hydrogel system, and a composite material with excellent mechanical properties and high-efficiency thermal protection functions is successfully prepared. The composite hydrogel is based on sodium alginate and polyvinyl alcohol. The rich hydroxyl and carboxyl groups on its molecular chain not only give the material good hydrophilicity, but also facilitate cross-linking reactions with other monomers. Acrylamide and 2-acrylamide-2-methylpropanesulfonic acid are selected as the main monomers, and nano-hydroxyapatite is introduced as a reinforcing component. Acrylamide, as an important raw material for polymer synthesis, can effectively improve the stability of composite thermal insulation materials; while nanohydroxyapatite, with its inorganic inert structure, significantly enhances the heat resistance and flame retardancy of the hydrogel. Furthermore, physical crosslinking is used to evenly disperse nanohydroxyapatite and glass fiber within the hydrogel network, not only making the crosslinked structure denser but also further enhancing the mechanical strength and thermal insulation effect of the thermal insulation material, thereby more effectively suppressing the risk of thermal runaway in lithium-ion battery modules. Boron carbide increases thermal conductivity within the hydrogel, providing heat dissipation capabilities, while glass fiber acts as a thermal insulator within the hydrogel, thus forming a synergistic thermal conductivity-insulation mechanism to suppress the propagation of thermal runaway in lithium-ion battery modules.
[0039] like Figure 1 As shown, the thermal runaway device used in this invention primarily includes a battery module, thermocouples, a heating rod, a battery cycler, an electronic balance, a GoPro camera, a temperature control box, an information processing system, and a computer. A three-row, three-column battery module was assembled using eight NCM811-18650 lithium-ion batteries and a cylindrical heating rod. The battery was fully charged using a battery cycler. Thermal runaway (TR) was induced by overheating the heating rod, with the heating temperature controlled by a temperature control box. Thermocouples were attached to the battery and heating rod to collect temperature data, and a balance was used to record the mass change of the battery module during the experiment. All data was collected by the information processing system and transmitted to the computer. The experimental phenomena were recorded by the GoPro camera.
[0040] The present invention is described in detail below with reference to specific embodiments.
[0041] Example 1:
[0042] This embodiment provides a method for preparing a composite thermal insulation material for inhibiting the propagation of thermal runaway in lithium-ion batteries, which specifically includes the following steps:
[0043] Step 1: mixing the sodium alginate solution and the polyvinyl alcohol solution to obtain a mixed solution 1;
[0044] 1.6 g of sodium alginate and 2 g of polyvinyl alcohol (6 portions) were weighed and dissolved in 300 ml of deionized water. The dissolution temperature of sodium alginate was 80° C. The temperature was then raised to 92° C. to dissolve the polyvinyl alcohol. After the polyvinyl alcohol was completely dissolved, a mixed solution 1 was obtained.
[0045] Step 2: Cool to room temperature, add nanohydroxyapatite to the mixed solution 1, and place it in an ultrasonic device for ultrasonic treatment for 15 minutes. Then, place the mixed solution obtained by ultrasonic treatment in a water bath at 55°C to ensure that the nanohydroxyapatite is evenly dispersed, thereby obtaining a mixed solution 2.
[0046] Step 3: 4 g acrylamide and 2 g 2-acrylamide-2-methylpropanesulfonic acid were added to the mixed solution 2 in sequence, and the mixture was stirred in a 55° C. water bath for 15 min until uniformly stirred to obtain a mixed solution 3.
[0047] Step 4. Boron carbide nanosheets are added to the mixed solution 3 at 0 g / L, 1.33 g / L, 2.67 g / L, 4 g / L, 5.33 g / L and 6.67 g / L, respectively, and the pH is adjusted to 5-7. The mixed solution 4 is obtained by stirring at a certain temperature. The phosphate in the nanohydroxyapatite and the cations on the surface of the boron carbide generate electrostatic attraction to form ionic bonds, and the boron atoms on the surface of the boron carbide form coordination bonds with the oxygen in the phosphate or hydroxide of the nanohydroxyapatite.
[0048] Step 5: adding glass fiber to the mixed solution 4, placing the mixed solution in an ultrasonic device for 30 minutes, and then placing the mixed solution obtained by ultrasonic treatment in a water bath at 50-60° C. to ensure that the glass fiber is evenly dispersed, thereby obtaining a mixed solution 5;
[0049] Step six, place the mixed solution five in a constant temperature water bath at a temperature of 55°C, stir at a certain speed, and slowly add the initiator ammonium persulfate to activate the active functional groups of sodium alginate, polyvinyl alcohol, acrylamide, and 2-acrylamide-2-methylpropanesulfonic acid through ammonium persulfate, causing a chain reaction and forming a long-chain structure. After stirring for 30 minutes, add the crosslinker MBA to the obtained hydrogel system to react, and introduce glass fiber into the hydrogel system by crosslinking. The thermal conductivity of boron carbide and the thermal insulation of glass fiber form a "thermal conduction-thermal insulation" mechanism to obtain a composite thermal insulation material.
[0050] The scanning electron microscope image of the raw glass fiber in this embodiment is as follows Figure 2 As shown in (a), the scanning electron microscope image of hydroxyapatite is as follows Figure 2As shown in (b), when the amount of nano-hydroxyapatite added in this embodiment is 5.33 g / L, the scanning electron microscope image of the prepared composite thermal insulation material is as follows: Figure 2 As shown in (d) and (e), the transmission electron microscope images of the composite thermal insulation material are as follows Figure 2 As shown in (f).
[0051] Example 2:
[0052] This embodiment provides a method for preparing a composite thermal insulation material for inhibiting the propagation of thermal runaway in lithium-ion batteries, which specifically includes the following steps:
[0053] Step 1: mixing the sodium alginate solution and the polyvinyl alcohol solution to obtain a mixed solution 1;
[0054] 1.6 g of sodium alginate was weighed out in 6 portions respectively and dissolved in 300 mL of deionized water. The mixture was magnetically stirred in a water bath at 80° C. to completely dissolve the mixture. Then, polyvinyl alcohol was added to each sodium alginate solution at 5.33 g / L, 6 g / L, 6.67 g / L, 7.33 g / L and 8 g / L, respectively. The mixture was magnetically stirred in a water bath at 92° C. until the mixture was completely dissolved to obtain a mixed solution 1.
[0055] Step 2: Cool to room temperature, add 1.6 g of nanohydroxyapatite to the mixed solution 1, and place it in an ultrasonic device for ultrasonic treatment for 15 minutes. Then, place the mixed solution obtained by ultrasonic treatment in a water bath at 55°C to ensure that the nanohydroxyapatite is evenly dispersed, to obtain a mixed solution 2.
[0056] Step 3: 4 g acrylamide and 2 g 2-acrylamide-2-methylpropanesulfonic acid were added to the mixed solution 2 in sequence, and the mixture was stirred in a 55° C. water bath for 15 min until uniformly stirred to obtain a mixed solution 3.
[0057] Step 4: Add 5.33 g / L boron carbide nanosheets to the mixed solution 3, adjust the pH to 5-7, and stir thoroughly under certain temperature conditions to obtain a mixed solution 4. The phosphate in the nanohydroxyapatite and the cations on the surface of the boron carbide generate electrostatic attraction to form ionic bonds, and the boron atoms on the surface of the boron carbide form coordination bonds with the oxygen in the phosphate or hydroxide of the nanohydroxyapatite.
[0058] Step 5: adding glass fiber to the mixed solution 4, placing the mixed solution in an ultrasonic device for 30 minutes, and then placing the mixed solution obtained by ultrasonic treatment in a water bath at 50-60° C. to ensure that the glass fiber is evenly dispersed, thereby obtaining a mixed solution 5;
[0059] Step six, place the mixed solution five in a constant temperature water bath at a temperature of 55°C, stir at a certain speed, and slowly add the initiator ammonium persulfate to activate the active functional groups of sodium alginate, polyvinyl alcohol, acrylamide, and 2-acrylamide-2-methylpropanesulfonic acid through ammonium persulfate, causing a chain reaction and forming a long-chain structure. After stirring for 30 minutes, add the crosslinker MBA to the obtained hydrogel system to react, and introduce glass fiber into the hydrogel system by crosslinking. The thermal conductivity of boron carbide and the thermal insulation of glass fiber form a "thermal conduction-thermal insulation" mechanism to obtain a composite thermal insulation material.
[0060] Example 3:
[0061] This embodiment provides a method for preparing a composite thermal insulation material for inhibiting the propagation of thermal runaway in lithium-ion batteries, which specifically includes the following steps:
[0062] Step 1: mixing the sodium alginate solution and the polyvinyl alcohol solution to obtain a mixed solution 1;
[0063] 6 parts of sodium alginate were weighed according to the amount of 3.33 g / L, 4 g / L, 4.67 g / L, 5.33 g / L and 6 g / L, respectively, and dissolved in 300 mL of deionized water. The mixture was magnetically stirred in a water bath at 80°C until it was completely dissolved. Then, 2 g of polyvinyl alcohol was added to the 6 parts of sodium alginate solution in sequence, and the mixture was magnetically stirred in a water bath at 92°C until it was completely dissolved to obtain a mixed solution 1.
[0064] Step 2: Cool to room temperature, add 1.6 g of nanohydroxyapatite to the mixed solution 1, and place it in an ultrasonic device for ultrasonic treatment for 15 minutes. Then, place the mixed solution obtained by ultrasonic treatment in a water bath at 55°C to ensure that the nanohydroxyapatite is evenly dispersed, to obtain a mixed solution 2.
[0065] Step 3: 4 g acrylamide and 2 g 2-acrylamide-2-methylpropanesulfonic acid were added to the mixed solution 2 in sequence, and the mixture was stirred in a 55° C. water bath for 15 min until uniformly stirred to obtain a mixed solution 3.
[0066] Step 4: Add 5.33 g / L boron carbide nanosheets to the mixed solution 3, adjust the pH to 5-7, and stir thoroughly under certain temperature conditions to obtain a mixed solution 4. The phosphate in the nanohydroxyapatite and the cations on the surface of the boron carbide generate electrostatic attraction to form ionic bonds, and the boron atoms on the surface of the boron carbide form coordination bonds with the oxygen in the phosphate or hydroxide of the nanohydroxyapatite.
[0067] Step 5: adding glass fiber to the mixed solution 4, placing the mixed solution in an ultrasonic device for 30 minutes, and then placing the mixed solution obtained by ultrasonic treatment in a water bath at 50-60° C. to ensure that the glass fiber is evenly dispersed, thereby obtaining a mixed solution 5;
[0068] Step six, place the mixed solution five in a constant temperature water bath at a temperature of 55°C, stir at a certain speed, and slowly add the initiator ammonium persulfate to activate the active functional groups of sodium alginate, polyvinyl alcohol, acrylamide, and 2-acrylamide-2-methylpropanesulfonic acid through ammonium persulfate, causing a chain reaction and forming a long-chain structure. After stirring for 30 minutes, add the crosslinker MBA to the obtained hydrogel system to react, and introduce glass fiber into the hydrogel system by crosslinking. The thermal conductivity of boron carbide and the thermal insulation of glass fiber form a "thermal conduction-thermal insulation" mechanism to obtain a composite thermal insulation material.
[0069] Example 4:
[0070] This embodiment provides a method for preparing a composite thermal insulation material for inhibiting the propagation of thermal runaway in lithium-ion batteries, which specifically includes the following steps:
[0071] Step 1: mixing the sodium alginate solution and the polyvinyl alcohol solution to obtain a mixed solution 1;
[0072] 1.6 g of sodium alginate and 2 g of polyvinyl alcohol were dissolved in 300 ml of deionized water. The dissolution temperature of sodium alginate was 80° C. The temperature was then raised to 92° C. to dissolve the polyvinyl alcohol. After the polyvinyl alcohol was completely dissolved, a mixed solution 1 was obtained.
[0073] Step 2: Cool to room temperature, add different masses of nanohydroxyapatite to the mixed solution one, namely 0, 0.4, 0.8, 1.2, 1.6, and 2.0 g, respectively, and place in an ultrasonic device for ultrasonic treatment for 15 minutes. Then, place the mixed solution obtained by ultrasonic treatment in a water bath at 55°C to ensure that the nanohydroxyapatite is evenly dispersed, to obtain a mixed solution two.
[0074] Step 3: 4 g acrylamide and 2 g 2-acrylamide-2-methylpropanesulfonic acid were added to the mixed solution 2 in sequence, and the mixture was stirred in a 55° C. water bath for 15 min until uniformly stirred to obtain a mixed solution 3.
[0075] Step 4. Boron carbide nanosheets are added to the mixed solution 3 at 0 g / L, 1.33 g / L, 2.67 g / L, 4 g / L, 5.33 g / L and 6.67 g / L, respectively, and the pH is adjusted to 5-7. The mixed solution 4 is obtained by stirring at a certain temperature. The phosphate in the nanohydroxyapatite and the cations on the surface of the boron carbide generate electrostatic attraction to form ionic bonds, and the boron atoms on the surface of the boron carbide form coordination bonds with the oxygen in the phosphate or hydroxide of the nanohydroxyapatite.
[0076] Step 5: adding glass fiber to the mixed solution 4, placing the mixed solution in an ultrasonic device for 30 minutes, and then placing the mixed solution obtained by ultrasonic treatment in a water bath at 50-60° C. to ensure that the glass fiber is evenly dispersed, thereby obtaining a mixed solution 5;
[0077] Step six, place the mixed solution five in a constant temperature water bath at a temperature of 55°C, stir at a certain speed, and slowly add the initiator ammonium persulfate to activate the active functional groups of sodium alginate, polyvinyl alcohol, acrylamide, and 2-acrylamide-2-methylpropanesulfonic acid through ammonium persulfate, causing a chain reaction and forming a long-chain structure. After stirring for 30 minutes, add the crosslinker MBA to the obtained hydrogel system to react, and introduce glass fiber into the hydrogel system by crosslinking. The thermal conductivity of boron carbide and the thermal insulation of glass fiber form a "thermal conduction-thermal insulation" mechanism to obtain a composite thermal insulation material.
[0078] Comparative Example 1:
[0079] The preparation method of the composite thermal insulation material includes:
[0080] Step 1: mixing the sodium alginate solution and the polyvinyl alcohol solution to obtain a mixed solution 1;
[0081] 1.6 g of sodium alginate and 2 g of polyvinyl alcohol (6 portions) were weighed and dissolved in 300 ml of deionized water. The dissolution temperature of sodium alginate was 80° C. The temperature was then raised to 92° C. to dissolve the polyvinyl alcohol. After the polyvinyl alcohol was completely dissolved, a mixed solution 1 was obtained.
[0082] Step 2: Cool to room temperature, add nanohydroxyapatite to the mixed solution 1, and place it in an ultrasonic device for ultrasonic treatment for 15 minutes. Then, place the mixed solution obtained by ultrasonic treatment in a water bath at 55°C to ensure that the nanohydroxyapatite is evenly dispersed, thereby obtaining a mixed solution 2.
[0083] Step 3: 4 g acrylamide and 2 g 2-acrylamide-2-methylpropanesulfonic acid were added to the mixed solution 2 in sequence, and the mixture was stirred in a 55° C. water bath for 15 min until uniformly stirred to obtain a mixed solution 3.
[0084] Step 4: Add 5.33 g / L boron carbide nanosheets to the mixed solution 3, adjust the pH to 5-7, and stir thoroughly under certain temperature conditions to obtain a mixed solution 4. The phosphate in the nanohydroxyapatite and the cations on the surface of the boron carbide generate electrostatic attraction to form ionic bonds, and the boron atoms on the surface of the boron carbide form coordination bonds with the oxygen in the phosphate or hydroxide of the nanohydroxyapatite.
[0085] Step 5. Place the mixed solution 4 in a constant temperature water bath at 55°C, stir at a certain speed, and slowly add the initiator ammonium persulfate to activate the active functional groups of sodium alginate, polyvinyl alcohol, acrylamide, and 2-acrylamide-2-methylpropanesulfonic acid through ammonium persulfate, causing a chain reaction and forming a long-chain structure. After stirring for 30 minutes, add the crosslinker MBA to the obtained hydrogel system to react. The thermal conductivity of boron carbide and the thermal insulation of glass fiber form a "thermal conduction-thermal insulation" mechanism to obtain a composite thermal insulation material.
[0086] Comparative Example 2:
[0087] The preparation method of the composite thermal insulation material includes:
[0088] Step 1: mixing the sodium alginate solution and the polyvinyl alcohol solution to obtain a mixed solution 1;
[0089] 1.6 g of sodium alginate and 2 g of polyvinyl alcohol (6 portions) were weighed and dissolved in 300 ml of deionized water. The dissolution temperature of sodium alginate was 80° C. The temperature was then raised to 92° C. to dissolve the polyvinyl alcohol. After the polyvinyl alcohol was completely dissolved, a mixed solution 1 was obtained.
[0090] Step 2: Cool to room temperature, add nanohydroxyapatite to the mixed solution 1, and place it in an ultrasonic device for ultrasonic treatment for 15 minutes. Then, place the mixed solution obtained by ultrasonic treatment in a water bath at 55°C to ensure that the nanohydroxyapatite is evenly dispersed, thereby obtaining a mixed solution 2.
[0091] Step 3: 4 g acrylamide and 2 g 2-acrylamide-2-methylpropanesulfonic acid were added to the mixed solution 2 in sequence, and the mixture was stirred in a 55° C. water bath for 15 min until uniformly stirred to obtain a mixed solution 3.
[0092] Step 4: adding glass fiber to the mixed solution 3, placing the mixed solution in an ultrasonic device for 30 minutes, and then placing the mixed solution obtained by ultrasonic treatment in a water bath at 50-60° C. to ensure that the glass fiber is evenly dispersed, thereby obtaining a mixed solution 4;
[0093] Step 6. Place the mixed solution 4 in a constant temperature water bath at 55°C, stir at a certain speed, and slowly add the initiator ammonium persulfate to activate the active functional groups of sodium alginate, polyvinyl alcohol, acrylamide, and 2-acrylamide-2-methylpropanesulfonic acid through ammonium persulfate, causing a chain reaction and forming a long chain structure. After stirring for 30 minutes, add the crosslinker MBA to the obtained hydrogel system for reaction, and introduce the glass fiber into the hydrogel system by crosslinking to obtain a composite thermal insulation material.
[0094] Comparative Example 3:
[0095] The preparation method of the composite thermal insulation material includes:
[0096] Step 1: mixing the sodium alginate solution and the polyvinyl alcohol solution to obtain a mixed solution 1;
[0097] 1.6 g of sodium alginate and 2 g of polyvinyl alcohol (6 portions) were weighed and dissolved in 300 ml of deionized water. The dissolution temperature of sodium alginate was 80° C. The temperature was then raised to 92° C. to dissolve the polyvinyl alcohol. After the polyvinyl alcohol was completely dissolved, a mixed solution 1 was obtained.
[0098] Step 3: 4 g acrylamide and 2 g 2-acrylamide-2-methylpropanesulfonic acid were added to the mixed solution 1 in sequence, and the mixture was stirred in a water bath at 55° C. for 15 min until uniformly stirred to obtain a mixed solution 2.
[0099] Step 4: Add glass fiber to the mixed solution 2, place it in an ultrasonic device for ultrasonic treatment for 30 minutes, and then place the mixed solution obtained by ultrasonic treatment in a water bath at 50-60° C. to ensure that the glass fiber is evenly dispersed, to obtain a mixed solution 3;
[0100] Step 6. Place the mixed solution 3 in a constant temperature water bath at 55°C, stir at a certain speed, and slowly add the initiator ammonium persulfate to activate the active functional groups of sodium alginate, polyvinyl alcohol, acrylamide, and 2-acrylamide-2-methylpropanesulfonic acid through ammonium persulfate, causing a chain reaction and forming a long chain structure. After stirring for 30 minutes, add the crosslinker MBA to the obtained hydrogel system for reaction, and introduce the glass fiber into the hydrogel system by crosslinking to obtain a composite thermal insulation material.
[0101] Comparative Example 4:
[0102] The preparation method of the composite thermal insulation material includes:
[0103] Step 1: mixing the sodium alginate solution and the polyvinyl alcohol solution to obtain a mixed solution 1;
[0104] 1.6 g of sodium alginate and 2 g of polyvinyl alcohol (6 portions) were weighed and dissolved in 300 ml of deionized water. The dissolution temperature of sodium alginate was 80° C. The temperature was then raised to 92° C. to dissolve the polyvinyl alcohol. After the polyvinyl alcohol was completely dissolved, a mixed solution 1 was obtained.
[0105] Step 2: Cool to room temperature, add nanohydroxyapatite to the mixed solution 1, and place it in an ultrasonic device for ultrasonic treatment for 15 minutes. Then, place the mixed solution obtained by ultrasonic treatment in a water bath at 55°C to ensure that the nanohydroxyapatite is evenly dispersed, thereby obtaining a mixed solution 2.
[0106] Step 3: 4 g acrylamide and 2 g 2-acrylamide-2-methylpropanesulfonic acid were added to the mixed solution 2 in sequence, and the mixture was stirred in a 55° C. water bath for 15 min until uniformly stirred to obtain a mixed solution 3.
[0107] Step 4: Place the mixed solution 3 in a constant temperature water bath at 55°C, stir at a certain speed, and slowly add the initiator ammonium persulfate to activate the active functional groups of sodium alginate, polyvinyl alcohol, acrylamide, and 2-acrylamide-2-methylpropanesulfonic acid through ammonium persulfate, causing a chain reaction and forming a long chain structure. After stirring for 30 minutes, add the crosslinker MBA to the obtained hydrogel system to react to obtain a composite thermal insulation material.
[0108] Application testing:
[0109] The composite thermal insulation materials obtained in the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 4 of the present invention are Figure 1 Thermal runaway experimental device for performance testing.
[0110] First, thermal gravimetric testing
[0111] The thermal decomposition behavior of the material was characterized using thermogravimetric-differential scanning calorimetry (TG-DSC, SDT Q600). Before the experiment, the final product was dried in a vacuum oven. A 9mg sample powder was accurately weighed and placed in a high-temperature thermogravimetric analyzer (TGA 11600HT) under a nitrogen atmosphere to test its thermal stability and evaluate the thermal decomposition characteristics of the material.
[0112] from Figure 3 From (a), it can be concluded that the main thermal decomposition temperatures of the composite hydrogel without hydroxyapatite are 314°C and 388°C, and a large mass loss occurs when the temperature rises to the range of 300°C-400°C. Figure 3 From (b), it can be concluded that the primary thermal decomposition temperatures of the composite insulation material occur at 89°C, 296°C, 389°C, and 431°C, respectively. Comparing the two sets of data reveals that the residual mass of the composite insulation material without hydroxyapatite at 650°C is only 30.5%, and this remains on a decreasing trend. However, after the addition of hydroxyapatite, the residual mass of the composite insulation material at the same temperature increases to 46.2% and stabilizes, with a 16.2% reduction in mass loss. This result demonstrates that the addition of hydroxyapatite significantly enhances the thermal stability of the composite insulation material, enabling it to maintain good structural integrity even in high-temperature environments, thus ensuring its practical performance.
[0113] Second, mechanical properties test
[0114] Traditional sodium alginate (SA)-based hydrogels are limited in application due to their insufficient mechanical properties, so enhancing their mechanical strength is crucial to expanding their practical applications. Figure 4Experimental data in (a) and (b) show that the compressive properties of the composite insulation material are significantly improved compared to samples without hydroxyapatite. When the hydroxyapatite content reaches 5.3g / L, the compressive strength of the composite insulation material reaches a peak of 36.23MPa, a value far exceeding the mechanical properties of common insulation materials such as extruded polystyrene boards. These excellent mechanical properties are due to the material's unique structural design: on the one hand, hydroxyapatite strengthens the hydrogel's skeleton stability through hydrogen bonding and metal coordination effects; on the other hand, the polymer chains entangle with each other to form a dense three-dimensional network. This dual network structure is similar to building a "protective armor" for the hydrogel, in which the rigid exoskeleton formed by hydroxyapatite and the flexible polymer network work synergistically to improve the overall mechanical properties of the composite insulation material.
[0115] Mechanical properties of the composite insulating water gels prepared in Comparative Examples 3 and 4 were tested. The results showed that the maximum compressive strength of the composite insulating water gel prepared in Comparative Example 3, which did not include boron carbide and hydroxyapatite, was 24.46 MPa, a 32.5% decrease compared to the final product. The maximum compressive strength of the composite insulating water gel prepared in Comparative Example 4, which did not include boron carbide and glass fiber, was 30.78 MPa, a 15.1% decrease compared to the final product. This demonstrates that the multiple raw materials used in the present invention can synergistically enhance the mechanical properties of the composite insulating water gel.
[0116] Third, battery thermal runaway propagation test
[0117] Temperature response analysis combined with thermal runaway propagation experiments Figures 5 to 10 As shown in the figure, during the central heating test, in a module without protective measures, when the temperature of the heating rod continued to rise, the 1-2, 2-1, 2-3 and 3-2 batteries adjacent to the heat source experienced thermal runaway in the 2071-2112s range. Once thermal runaway was triggered, the temperature of other batteries in the module rose sharply within 35s, as shown in the figure. Figure 5 As shown in the figure, the average triggering time is 2109s and the peak temperature is as high as 894℃. Since the heat source is located in the center and is in direct contact with the four batteries, the thermal runaway propagates fastest and is the most severe. The results of the central heating test using a 4mm thick composite hydrogel protection show that Figure 6 As shown in the figure, although the thermal runaway of adjacent batteries could not be completely prevented, the thermal runaway propagation of the remote diagonal battery was successfully blocked. The water in the hydrogel significantly delayed the temperature rise process by continuously absorbing heat, delaying the average trigger time of adjacent batteries to 3551s (1442s longer than the blank group), the maximum temperature dropped to 584.8℃, the maximum temperature difference in the module was 485.6℃, and the temperature of the corner batteries was always maintained below 103.1℃. In the comparative experiment of the side heating mode, the blank control group showed that Figure 7As shown in the figure, the three batteries closest to the heat source experienced thermal runaway within 50 seconds, and then all the batteries in the module were ignited within 100 seconds. The average triggering time was 1702 seconds and the highest temperature was 721.7℃. The test results after using hydrogel protection. Figure 8 As shown in the figure, only three adjacent batteries experienced thermal runaway, the average triggering time was extended to 3021s (1319s longer than the blank group), the maximum temperature dropped to 583.3℃, and the maximum temperature difference was 477.9℃. Figure 9 As shown in the figure, after the two batteries adjacent to the heat source triggered thermal runaway, the third battery was triggered to runaway within 100 seconds, with an average triggering time of 1975 seconds. The corner heating test results after using hydrogel protection showed that only two adjacent batteries ranaway, and the triggering time was delayed to 3380 seconds (extended by 1405 seconds), with a maximum temperature difference of 510.4°C. Figure 10 shown.
[0118] Experimental data show that: (1) the number of batteries in direct contact with the heat source is positively correlated with the severity of thermal runaway; (2) composite thermal insulation materials can effectively delay the triggering time of thermal runaway (extending 1319 to 1442 seconds); (3) significantly reduce the peak temperature of runaway batteries (by 138.9 to 309.2°C); and (4) effectively control the temperature rise rate of batteries that do not run away.
[0119] The thermal runaway propagation suppression performance of the composite insulation materials prepared in Comparative Examples 3 and 4 was tested. The test results showed that when a 4mm thick composite insulating hydrogel without boron carbide and nano-hydroxyapatite was used for protection, the triggering time of thermal runaway in adjacent batteries was delayed by 945 to 1134 seconds. When a 4mm thick composite insulating hydrogel without boron carbide and glass fiber was used for protection, the triggering time of thermal runaway in adjacent batteries was delayed by 796 to 989 seconds. This shows that the boron carbide in the hydrogel system can work together with hydroxyapatite and glass fiber to effectively protect the interior of the battery module, achieving a synergistic effect of suppressing the propagation of thermal runaway in the battery module.
[0120] Parts not described in the present invention can be implemented by referring to the existing technology.
[0121] Those skilled in the art should recognize that the above embodiments are merely intended to illustrate the present application and are not intended to limit the present application. As long as they are within the spirit of the present application, appropriate changes and modifications to the above embodiments are within the scope of protection claimed in the present application.
Claims
1. A method for preparing a composite thermal insulation material for inhibiting the propagation of thermal runaway of lithium-ion batteries, characterized in that: The following steps are involved: a. mixing the sodium alginate solution and the polyvinyl alcohol solution to obtain a mixed solution 1; b. Adding nano-hydroxyapatite to the mixed solution 1 and placing it in an ultrasonic device for ultrasonic treatment, then placing the ultrasonically treated mixed solution in a water bath at 50-60° C. to ensure that the nano-hydroxyapatite is evenly dispersed, to obtain a mixed solution 2; c. adding acrylamide and 2-acrylamide-2-methylpropanesulfonic acid to the mixed solution II in sequence, and stirring uniformly to obtain a mixed solution III; d. Adding boron carbide nanosheets to the mixed solution (3), adjusting the pH to 5-7, and fully stirring under certain temperature conditions to obtain a mixed solution (4). The phosphate in the nanohydroxyapatite and the cations on the surface of the boron carbide generate electrostatic attraction to form ionic bonds, and the boron atoms on the surface of the boron carbide form coordination bonds with the oxygen in the phosphate or hydroxide of the nanohydroxyapatite. e. Adding glass fiber to the mixed solution (4) and placing the solution in an ultrasonic device for ultrasonic treatment. Then, placing the resulting mixed solution in a water bath at 50-60° C. to ensure uniform dispersion of the glass fiber, thereby obtaining a mixed solution (5); f. Slowly add ammonium persulfate as an initiator to the mixed solution five, and activate the active functional groups of sodium alginate, polyvinyl alcohol, acrylamide, and 2-acrylamide-2-methylpropanesulfonic acid through the ammonium persulfate, causing a chain reaction and forming a long-chain structure. Then, add a cross-linking agent to the resulting hydrogel system for reaction, and introduce glass fiber into the hydrogel system through cross-linking. The thermal conductivity of boron carbide and the thermal insulation of glass fiber form a "thermal conduction-thermal insulation" mechanism to obtain a composite thermal insulation material.
2. The method for preparing a composite thermal insulation material for inhibiting the propagation of thermal runaway of a lithium-ion battery according to claim 1, characterized in that: In step a, the mass fraction ratio of the sodium alginate solution to the polyvinyl alcohol solution is 0.8:1; the sodium alginate solution is prepared by adding sodium alginate to deionized water, the mass volume ratio of sodium alginate to deionized water is 1.6:300 g / L, and the dissolution temperature is 70-75°C; the polyvinyl alcohol solution is prepared by adding polyvinyl alcohol to deionized water, the mass volume ratio of polyvinyl alcohol to deionized water is 2:300 g / L.
3. The method for preparing a composite thermal insulation material for inhibiting the propagation of thermal runaway of a lithium-ion battery according to claim 1, characterized in that: In step b, the mass ratio of nano-hydroxyapatite to sodium alginate is 1:
1.
4. The method for preparing a composite thermal insulation material for inhibiting the propagation of thermal runaway of a lithium-ion battery according to claim 1, characterized in that: In step c, the mass ratio of acrylamide to sodium alginate is 1:0.4, and the mass ratio of acrylic amine to 2-acrylamide-2-methylpropanesulfonic acid is 2:1; and the temperature is maintained at 50-60° C. during stirring.
5. The method for preparing a composite thermal insulation material for inhibiting the propagation of thermal runaway of a lithium-ion battery according to claim 4, characterized in that: In step d, the mass ratio of the added amount of boron carbide nanosheets to 2-acrylamide-2-methylpropanesulfonic acid is 1:1, and the temperature is controlled at 50-60° C. during stirring.
6. The method for preparing a composite thermal insulation material for suppressing the propagation of thermal runaway of a lithium-ion battery according to claim 5, characterized in that: In step e, the mass ratio of the glass fiber to the boron carbide is 5:
2.
7. The method for preparing a composite thermal insulation material for inhibiting the propagation of thermal runaway of a lithium-ion battery according to claim 6, characterized in that: In step f, the mixed solution five is placed in a constant temperature water bath at a temperature of 60-65° C., and the mass ratio of ammonium persulfate to glass fiber is 0.009:
1.
8. The method for preparing a composite thermal insulation material for inhibiting the propagation of thermal runaway of a lithium-ion battery according to claim 1, characterized in that: In step f, the cross-linking agent is N,N-methylenebisacrylamide, the mass ratio of N,N-methylenebisacrylamide to ammonium persulfate is 0.38:0.045, the reaction temperature after adding the cross-linking agent is 60-65° C., and the reaction is carried out for 2-4 hours.
9. Use of the composite thermal insulation material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: When the composite thermal insulation material is in direct contact with a heat source, it can effectively delay the triggering time of thermal runaway, reduce the peak temperature of the runaway battery, and effectively control the temperature rise rate of the non-runaway battery.
Citation Information
Patent Citations
Metal coating and production method thereof
CN106854423A
High-efficiency flame-retardant material
CN110527299A
Lithium ion battery and preparation method thereof
CN114024097A
KR20240078073A